Inter-chromosomal recombination of Mll and Af9 genes mediated by cre-loxP in mouse development. - Collins, E; Pannell, R; Simpson, E; Forster, A; Rabbitts, T (2000)
Chromosomal translocations are crucial events in the aetiology of many leukaemias, lymphomas and sarcomas, resulting in enforced oncogene expression or the creation of novel fusion genes. The study of the biological outcome of such events ideally requires recapitulation of the tissue specificity and timing of the chromosomal translocation itself. We have used the Cre-loxP system of phage P1 to induce de novo Mll-Af9 chromosomal recombination during mouse development. loxP sites were introduced into the Mll and Af9 genes on chromosomes 9 and 4, respectively, and mice carrying these alleles were crossed with mice expressing Cre recombinase. A resulting Mll-Af9 fusion gene was detected whose transcription and splicing were verified. Thus, programmed interchromosomal recombination can be achieved in mice. This approach should allow the design of mouse models of tumorigenesis with greater biological relevance than those available at present.